Use of liposomes in the diagnosis and treatment of non-melanoma skin cancer: an integrative review (Research, Society and Development, 2022)
Non-melanoma skin cancer (NMSC) is the type of cancer with the highest incidence and has been classified into: basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). The aim of the present study was to evaluate, through an integrative literature review, the use of liposomes in the diagnosis and treatment of NMSC. The search strategy for scientific articles was carried out through an investigation in the Scopus, Pubmed and Web Of Science databases, accessing through the Capes Periodicals Portal, using the English descriptors "Liposomes" AND "non-melanoma" AND "skin" AND “cancer” AND “(treatment OR diagnosis)”. To assist the process of analyzing the articles, the Rayyan platform was used. After analysis, 7 publications were selected to compose this review, identifying: titles, authors, objectives, main results, conclusions and topics addressed in the studies. It was observed that most of the thematic axes addressed the use of liposomal systems for the potentiation of drugs with antitumor capacity. The other articles discussed the use in the detection and diagnosis of lesions associated with Non-Melanoma Skin Cancer and also the application of nanocarriers in anticancer therapies, especially in photodynamic therapy. Based on this, it was concluded that liposomes have a versatile application in NMSC, ranging from treatment to diagnosis, however, research on the application focused on this topic is scarce and recent. Thus, this review is extremely relevant so that we can direct the elaboration of new studies that aim to improve the aforementioned techniques and develop new research on the subject.